Some hypotheses regarding the mobile telecommunications services marketing and consumers rights from Romania - Nicu Marcu; Georgeta-Mădălina Meghişan (Amfiteatru Economic Journal, 2013)
The current research analysis consumers' rights concerning personal data processing and confidentiality protection within the public communications sector as they are stated in the 2002/58/CE Directive of the European Parliament and Council from 12th of July 2002. The study objectives are: the way that users/ subscribers get informed about their rights in the field of mobile telephony services; the way that mobile telephony services operators inform their users/ subscribers about the subscription included services; the way that mobile telephony services operators inform their uses/ subscribers about the supplementary services that can be demanded; the rights regarding the personal data processing and confidentiality protection that mobile telephony services consumers agree with; the users/subscribers rights most frequently broken. The marketing research used a questionnaire based survey during January - March 2013 on a sample of 85 users/ subscribers from Romania. It has a preliminary character, shaping a further investigation activity with a higher thematic coverage and a smaller error under the limit of 5%. The data gathering method was a questionnaire based interview. Data were analyzed using the SPSS informatics program, version 16.0 for Windows. The following statistical functions were used for validating/invalidating the hypotheses: descriptive statistics, factor analysis and correlation function.
Keywords: M38; M31; M30; L86; L87; 330; research hypothesis; general economic services; mobile telecommunications services marketing; mobile telecommunications consumers' rights; marketing research